2005
DOI: 10.1002/j.2161-1882.2005.tb00072.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Client Stages of Change to Working Alliance and Outcome in Short-Term Counseling

Abstract: This study evaluated the relationship of J. O. Prochaska's (1984; J. O. Prochaska & C. C. DiClemente, 1992) transtheoretical model of change with the process and outcome of short‐term counseling in college help seekers. Participants completed measures of readiness to change, psychological symptoms, and working alliance. Clients in the precontemplation stage evaluated the working alliance less favorably and experienced less improvement regarding symptoms than clients in other stages. Counselor working alliance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 27 publications
3
15
1
Order By: Relevance
“…Principe et al (2006) provided a possible answer reporting that another variable, client stage of change, was significantly related to the alliance. Other researchers have reported similar findings, suggesting that client readiness for Contributing Factors in the Therapeutic Alliance 203 change at the outset of therapy is a determining factor for subsequent higher ratings of the therapeutic alliance (Rochlen, Rude, & Baron, 2005;Taft et al, 2004). In fact, Connors et al (2000) found client stage of change was one of only two variables positively related to the alliance for outpatients, and the only variable positively related to the alliance among aftercare patients.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Principe et al (2006) provided a possible answer reporting that another variable, client stage of change, was significantly related to the alliance. Other researchers have reported similar findings, suggesting that client readiness for Contributing Factors in the Therapeutic Alliance 203 change at the outset of therapy is a determining factor for subsequent higher ratings of the therapeutic alliance (Rochlen, Rude, & Baron, 2005;Taft et al, 2004). In fact, Connors et al (2000) found client stage of change was one of only two variables positively related to the alliance for outpatients, and the only variable positively related to the alliance among aftercare patients.…”
Section: Introductionsupporting
confidence: 61%
“…Finally, they noted decreasing scores on the precontemplation stage, in contrast to increasing scores on the other stages, represent an increasing readiness to change, implying a negative correlation with the other stages. Rochlen, Rude, and Baron (2005) found no difference between clients on these stages across any of their predictor or outcome variables, stating, "There may be little practical utility in distinguishing between the contemplation, maintenance, and action stages" (p. 60).…”
Section: Measures University Of Rhode Island Change Assessment (Urica)mentioning
confidence: 95%
“…This is one of the most commonly used methods (e.g., Derisley & Reynolds, 2000;Koraleski & Larson, 1997;Rochlen et al, 2005) and has been used in approximately 60% of previous studies on the stages and processes of change (Rosen, 2000). In this method, participants are assigned to one of the stages based on their highest subscale score.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, studies have found that it is very challenging to form a working relationship with clients who are reluctant to begin working on their problems or who are ambivalent about the change process (Bachelor & Horvath, 1999;Hatcher & Barends, 1996). Building off of these previous findings, recent research has shown that the stages of change are significantly correlated with the working alliance, with individuals in the higher stages of change reporting stronger working alliances than those in the lower stages of change (Principe, 2005;Rochlen et al, 2005;Taft, Murphy, Musser, & Remington, 2004;Treasure et al, 1999).…”
mentioning
confidence: 93%
See 1 more Smart Citation